Karakteristik Dadih Susu Kerbau Di Kecamatan Lembah Gumanti Dengan Paritas Induk Yang Berbeda - , Harissatria; Dara Surtina; John Hendri; Delsi Afrini (Rawa Sains: Jurnal Sains STIPER Amuntai, 2024)
Curd is one of the functional foods because it contains Lactic Acid Bacteria (LAB) as probiotic bacteria that are very beneficial for the health of the body which has been processed and consumed by the Minang people for decades. The purpose of this study was to assess the effect of different parent parities on pH values, protein content, fat content, calcium content and total colonies of buffalo milk curd bacteria in Solok Regency. The method used in this study was an experiment using a Completely Randomized Design (CRD) with 3 treatments, namely Parity 2, Parity 3 and Parity 4 with 5 replications. The results showed that the effect of parent parity did not have a significant effect (P>0.05) on the pH value of buffalo curd. significantly affected the protein content of buffalo curd (P<0.05). significantly affected the fat content of buffalo curd (P<0.05). significantly affected the calcium content of buffalo curd (P<0.05) and did not significantly affect (P>0.05) the total colonies of buffalo curd bacteria.